Ko-konstruktive Lerngespräche unter Grundschulkindern: Ergebnisse einer empirischen Studie zur sozialen Interaktion im Mathematikunterricht (mathematica didactica, 2014)
In the last years the demands that children should have more opportunities to discuss und reflect their solutions of a mathematical task with each other become louder and louder. Many current researches highlight the central importance of student participation in social interaction and call for student-centred, peer-based methods in mathematics classrooms. Consequently knowledge co-construction seems to be an important factor for individual learning. This article explores the nature of helping behaviour of third graders within co-constructive peer-directed small groups called „Mathekonferenz“ that may be effective for learning. Furthermore this paper gives hints to create the conditions to implement this method in mathematics learning and teaching in primary school.